Bringing the treatable traits approach to primary care asthma management - Pfeffer, Paul E.; Rupani, Hitasha; De Simoni, Anna (Frontiers in Allergy, 2023)
Despite an ever-growing range of treatments for asthma it continues to be a major cause of ill health with significant mortality. Adoption in specialist centres of the treatable-traits approach has underpinned improvements in asthma control and reductions in exacerbations in severe asthma. However most patients with asthma, particularly those with mild-to-moderate asthma, are managed in primary care according to guidelines that emphasise use of pharmacotherapeutic ladders uniformly implemented across all patients, more consistent with a ‘one-size-fits-all’ than a treatable-traits approach. This can be associated with harm, in particular in patients where symptoms and airway inflammation are discordant, and extra-pulmonary treatable-traits are often overlooked. Primary care has extensive experience in patient-centred holistic care and many aspects of the treatable-traits approach could be rapidly implemented in primary care. Blood eosinophil counts, as a biomarker of the treatable-trait of eosinophilia, are already included in routine haematology tests and could be used in primary care to guide titration of inhaled corticosteroids. Similarly, poor inhaler adherence could be further assessed and managed in primary care. However, research is needed to guide how some treatable-traits could feasibly be assessed and/or managed in primary care. For example, how best to manage in primary care patients with high reliever inhaler usage in the absence of raised T2 biomarkers, likely suffering from breathing patterns disorders and extra-pulmonary treatable-traits. Implementation of the treatable-traits approach across the disease severity spectrum will improve quality of life for patients with asthma but will take time and research to embed across care settings.